Kant's transcendental deduction of the categories : critical re-examination, elucidation & corroboration - Westphal, Kenneth R. (HUP, Helsinki University Press, 2021)
Immanuel Kant's 'Transcendental Deduction of the Categories' addresses issues centrally debated today in philosophy and in cognitive sciences, especially in epistemology, and in theory of perception. Kant's insights into these issues are clouded by pervasive misunderstandings of Kant's 'Deduction' and its actual aims, scope, and argument. The present edition with its fresh and accurate translation and concise commentary aims to serve these contemporary debates as well as continuing intensive and extensive scholarship on Kant's Critique of Pure Reason. Two surprising results are that 'Transcendental Deduction' is valid and sound, and it holds independently of Kant's transcendental idealism. This lucid volume is interesting and useful to students, yet sufficiently detailed to be informative to specialists.